A LITERATUR REVIEW : AKTIVITAS IMUNOMODULATOR PADA TANAMAN HERBAL - Yuliana, Dewi; Handayani, Dian Pratiwi; Purnamasari, Vina (PHARMACY UMI JOURNAL SYSTEM, 2024)
Health problems that often occur in Indonesia are problems related to diseases caused by free radicals. The presence of free radicals can trigger damage to cells and can disrupt the body's immune system. The immune system can be enhanced or suppressed, one way is by administering immunomodulators. Several natural compounds have the ability to increase immune system activity, including flavonoids, curcumin, limonoids, vitamin C, vitamin E and catechins. Phenolic components such as flavonoids and polyphenols can improve the immune system by increasing Interleukin-12 (IL-12) and lymphocyte proliferation. Based on the many health problems that arise in Indonesia due to the presence of free radicals, the aim of the research is to conduct a literature review on the mechanism of action of herbal plants as immunomodulators and the methods used to determine the mechanism of action of natural immunomodulators. The method used to review this article is to carry out an online search process using several search engines such as PubMed, Scopus, ProQuest and Schoolar. Based on reference studies, several herbal plant extracts act as immunomodulators with different activities such as increasing the activity of Immunoglobulin M (IgM), reducing the number of leukocytes, stimulating the body's immunity with flavonoid content and increasing the ability of phagocytosis.